Demand for payment services and consumer welfare: The introduction of a central bank digital currency - Kim P. Huynh; Jozsef Molnar; Oleksandr Shcherbakov; Qinghui Yu (Bank of Canada, 2020)
In recent years, there have been rapid technological innovations in retail payments. Such dramatic changes in the economics of payment systems have led to questions regarding whether there is consumer demand for cash. The entry of these new products and services has resulted in significant improvements in the characteristics of existing methods of payment, such as tap-and-go technology or contactless credit and debit cards. In addition, the introduction of decentralized digital currencies has raised questions about whether there is a need for a central bank digital currency (CBDC) and, if so, what its essential characteristics should be. To address these questions, we develop and estimate a structural model of demand for payment instruments. Our model allows for rich heterogeneity in consumer preferences. Identification of the distribution of consumer heterogeneity relies on observing individual-level consumer decisions at the point of sale. Using parameter estimates, we conduct a counterfactual experiment of an introduction of CBDC and simulate post-introduction consumer adoption and usage decisions. We also provide insights into the potential welfare implications of the introduction of new payment instruments.
Keywords: C51; E42; L14; L52; 330; Bank notes; Digital currencies and fintech; Financial services